2003
DOI: 10.1111/j.1939-1676.2003.tb02528.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Prognostic Significance of Radiographic Pattern, Distribution, and Severity of Thoracic Radiographic Changes in Neonatal Foals

Abstract: A total of 207 thoracic radiographs obtained from 128 foals were evaluated to assess the impact of pulmonary radiographic pattern, distribution, and severity of pulmonary changes on short-term survival of neonatal foals. The association between selected clinical variables and the radiographic manifestation of neonatal respiratory disease was also investigated. The evaluation of interstitial and alveolar-interstitial radiographic patterns within the caudodorsal, caudoventral, and cranioventral lung regions prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…pneumonia was 70%. Previous studies report survival of horses with bacterial pneumonia as low as 46% with more current studies reporting survival in up to 90% of cases . In our study, survival to discharge in horses <1 year of age was 79% (15/19), whereas overall survival to discharge in adults was 63% (17/27).…”
Section: Discussionsupporting
confidence: 37%
See 3 more Smart Citations
“…pneumonia was 70%. Previous studies report survival of horses with bacterial pneumonia as low as 46% with more current studies reporting survival in up to 90% of cases . In our study, survival to discharge in horses <1 year of age was 79% (15/19), whereas overall survival to discharge in adults was 63% (17/27).…”
Section: Discussionsupporting
confidence: 37%
“…Previous studies in foals found that a diagnosis of SIRS was associated with pulmonary infiltrates within the caudodorsal lung. 17 Interestingly, the most common distribution of radiographic lesions in adults and foals in this study was in the caudodorsal lung field. This finding may indicate that SIRS resulted in vascular and pulmonary damage in the caudodosal lung fields, which have increased perfusion when compared to the remainder of the lung.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Manipulation of the relative signal intensities of normal and abnormal tissue through appropriate use of MRI pulse sequences, the absence of ionizing radiation, and the ability to acquire images in nonaxial imaging planes are the relative advantages of MRI over CT (4,5). The evaluation of anatomic structures of the thorax is laborious due to its complex organization, which makes it difficult to diagnose morphologic alterations by means of physical examination and conventional radiographic studies (6). MRI may be a good alternative to conventional radiology.…”
Section: Introductionmentioning
confidence: 99%